THE DOSE ANALYSIS OF BORON NEUTRON CAPTURE THERAPY (BNCT) TO THE BRAIN CANCER (GLIOBLASTOMA MULTIFORM) USING MCNPX-CODE WITH NEUTRON SOURCE FROM COLLIMATED THERMAL COLUMN KARTINI RESEARCH NUCLEAR - Kholidah Hasyim; Yohannes Sardjono; Yosaphat Sumardi (Indonesian Journal of Physics and Nuclear Applications, 2018)
This research was aimed at discovering the optimum concentration of Boron-10 in concentrations range 20 µgram/gram until 35 µgram/gram with Boron Neutron Capture Therapy (BNCT) methods and the shortest time irradiation for cancer therapy. The research about dose analysis of Boron Neutron Capture Therapy (BNCT) to the brain cancer (Glioblastoma Multiform) using MCNPX-Code with a neutron source from Collimated Thermal Column Kartini Research Nuclear has been conducted. This research was a simulation-based experiment using MCNPX, and the data was arranged on a graph using OriginPro 8. The modelling was performed with the brain that contains cancer tissue as a target and the reactor as a radiation source. The variations of Boron concentrations in this research was on 20, 25, 30 and 35 μg/gram tumours. The outputs of MCNP were neutron scattering dose, gamma ray dose and neutron flux from the reactor. Neutron flux was used to calculate the doses of alpha, proton and gamma rays produced by the interaction of tissue material and thermal neutrons. Based on the calculations, the optimum concentration of Boron-10 in tumour tissue was for a 30 µg/gram tumour with the radiation dose in skin at less than 3 Gy. The irradiation times required were 2.79 hours for concentration 20 μg/gram ; 2.78 hours for concentration 25 μg/gram ; 2.77 hours for concentration 30 μg/gram ; 2.8 hours for concentration 35 μg/gram.